The sport/leisure revolution, the middle classes and the prospects for change - Sadi, Renato Sampaio (Seven Editora, 2023)
For a futuristic and revolutionary agenda in sports/leisureWorld trends, socio-economic and geopolitical, have revealed that the system of the functionality of capitalist societies is going through its worst crisis. To contribute to a  critical-purposeful,  academic, and professional debate in the field of education, political science, sociology, sport/leisure, and physical education, the future deserves to be thought of strategically. It is known that the speed of communication technologies as well as the willingness of social subjects the use and abuse digital tools has caused intense changes in labor relations and in the very way of being of the passivity with which we observe the new times, full of viruses, wars, catastrophes, etc. One could speculate on various ramifications of the current crisis by shielding oneself in a directionless critique or even create specific speculations restricted to local or regional microcosms. The proposal here is another: to reflect deeply on the next steps of the sensitive and human time of the workers in the perspective of seeking, in a fruitful way, intelligent trails for sport/leisure. This should provide diverse interests with a speculative and critical debate that can re-oxygenate the apathy with which we have faced political and emotional disorders. On the other hand, it must be said that revolutionizing sport/leisure will never be a non-neutral action. More than that: it is neither academic action in the traditional sense, nor is it a partisan political debate. Starting from Marxist and non-Marxist scientific bases, the debate will necessarily be critical, propositional, semi-utopian and, why not say, futuristic. In the movement of expansion of the new financialized and armed productive capital, capitalism has entered a new era, in which its new civilization will promote a historical break with the hitherto unknown evolution of this society. This is because, both in the US and Europe, right-wing politics and intellectuals have pushed the world towards an ultraliberalism of a fascist and strongly destructive character.  In Brazil, after the parliamentary coup of 2016, the Trump-Bolsonaro unity branched out in the people with the damage and ideological falsehoods. The perversity of capitalism impacts ecological systems and hinders the recreation of value. With this destroys productivity and its effects and consequences are felt more by the Global South. Such processes add to the militarism and militarism reigning in these neo-fascist and denialist times to renew the opportunities for the manufacture and sale of arsenals, bombs, airplanes, weapons, hatred, etc. Is the end near? What do sports/leisure and workers' hours of suffocation have to say about it? In the set of contradictions is it still possible to think of a liberated society, at least partially from alienated labor? The resistance of the people and the consequent agenda of tomorrow will be composed of what strategic contents? Amid the pulsating crossfire of this debate, this text calls for truly free work, impossible in capitalism. Reform and revolution are sides of a coin that constantly jumps in advanced consciousnesses, after all, which or what are the paths to the first steps of change? The pertinence of new communication and information technologies helps us to architect working hours, emancipation, vacations, regulation, and free time in a renewed perspective.  Cultural equipment and professional activities need to break through the frustrations of an alienated and perverse job that enslaves workers around the world. In the society of capital, sport/leisure serves interests that can make it an arm in favor of the masters, owners of gold. Could it be that much of what we have in the discourses cannot be active ammunition to dilute the toxicity of capitalism and the inherent contradictions of the order of capital?  (Harvey, 2017) DOI:https://doi.org/ 10.56238/devopinterscie-155